PROFIL USMAN BIN AFFAN DAN PEMERINTAHAN NEPOTIS - Syafri Gunawan (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2018)
Usman bin Affan was come from a noble family of Quraish. Since childhood he was known to have an admirable character, gentle, forgiving and wara '. He also included one of friends who provide material assistance to Islamic interests and fight for the establishment of Islam. He was known as one of the Khulafah Rasyidin. Six years from 12 years of his goverment appeared to feel disappointed among the Muslims. Among the factors that disappointment wa his wise to point his family to be a high position. Therefore, he was accused as a nepotistic. The appointment of state officials from among his family, not without reason. Usman lift them as state officials was that they were competent for the position and was based on the calculation and careful political wisdom to uphold and strengthen the position of amir al-mu'minin as the holder of the leadership of the country. With the two differents assessments it, then it could be said to have occurred misinterpretation of historical data